Pengaruh Gaya Hidup Aktif Melalui Pendidikan Jasmani Terhadap Prestasi Akademik Siswa - Ridwan, Andi; R, Andi Fathir Perawira; Rusli, Muhammad Aprilyansyah Pratama; Ulum, Muh. Bahrul; Rahim, Muh. Yusuf; Rustan, Muhammad Iqbal; Takdir, Muh. (Indo-MathEdu Intellectuals Journal, 2025)
Physical education plays an important role in shaping healthy lifestyle habits, improving physical fitness, and supporting the cognitive and emotional development of students. This study aims to describe the influence of an active lifestyle through physical education on students' academic achievement. This research uses a literature study method with a narrative or literature synthesis approach. Data sources come from national and international journal articles, especially recent publications after 2021, that discuss the relationship between physical activity, an active lifestyle, and students' academic achievement. The study results show that regular physical activity in physical education has a significant positive impact on academic achievement. Physical activity has been shown to improve cognitive functions such as concentration, memory, and problem-solving abilities, while also enhancing mental health by reducing stress and anxiety levels. Moreover, physical education supports the development of social skills, time management, and self-discipline, all of which contribute to academic success. These findings reinforce that physical education not only affects physical health but also plays an important role in students' academic development.